A broad phenotypic screen identifies novel phenotypes driven by a single mutant allele in Huntington's disease CAG knock-in mice. - Sabine M Hölter (Public Library of Science (PLoS), 2013)
Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by the expansion of a CAG trinucleotide repeat in the HTT gene encoding huntingtin. The disease has an insidious course, typically progressing over 10-15 years until death. Currently there is no effective disease-modifying therapy. To better understand the HD pathogenic process we have developed genetic HTT CAG knock-in mouse models that accurately recapitulate the HD mutation in man. Here, we describe results of a broad, standardized phenotypic screen in 10-46 week old heterozygous HdhQ111 knock-in mice, probing a wide range of physiological systems. The results of this screen revealed a number of behavioral abnormalities in HdhQ111/+ mice that include hypoactivity, decreased anxiety, motor learning and coordination deficits, and impaired olfactory discrimination. The screen also provided evidence supporting subtle cardiovascular, lung, and plasma metabolite alterations. Importantly, our results reveal that a single mutant HTT allele in the mouse is sufficient to elicit multiple phenotypic abnormalities, consistent with a dominant disease process in patients. These data provide a starting point for further investigation of several organ systems in HD, for the dissection of underlying pathogenic mechanisms and for the identification of reliable phenotypic endpoints for therapeutic testing.